Cooperative Patterns in the Egyptian Colloquial Arabic - Siti Aminah; Amir Ma'ruf (Humaniora, 2016)
This article described the cooperative patterns formed in the Egyptian speech community using Egyptian Colloquial Arabic (ECA). The data were taken by using participatory observation method  through  the  recording  and  note-taking  techniques.  By  employing  Grice’s  theory of cooperative principles and maxims, this study suggested that speech events in Egyptian society had a variety of cooperative patterns. The varied patterns could be seen in the negotiation processes to reach an agreement. Therefore, the negotiations required a lot of energy and time.